2016 AIChE Spring Meeting & 12th Global Congress on Process Safety : perspectives on process safety from around the globe (Center for Chemical Process Safety/AIChE, 2016)
The session chairs are interested in papers and presentations that describe approaches or programs designed to help facilitate the communication of technical engineering concepts and/or EHS related topics to internal and external non-technical stake holders (e.g. management, employees, regulators, education, and or public forms).
Prepared for Presentation at American Institute of Chemical Engineers 2016 Spring Meeting 12th Global Congress on Process Safety Houston, Texas April 11-23, 2016.
Keywords: Chemical process control.; Chemical plants -- Safety measures.; elektronické knihy; electronic books